Varstvo osebnostnih pravic obdolžencev pri medijskem poročanju o kazenskih postopkih - Šošić, Miha (Pravnik, 2015)
The media has an important function in modern democratic societies and a tremendous effect on the construction of social reality. It can play an important role of informing the public about ongoing criminal proceedings and in this way enable the control of civil society over the judiciary. The media can thus be helpful in ensuring a fair criminal trial, but only under the condition that the reporting on criminal proceedings is professional, unbiased, based on prudential research, and ensuring the personality rights of the trial participants are respected. Otherwise, the media can have an extremely negative effect on the conduct of a fair criminal trial. The public used to have an important role in protecting the defendant from arbitrary acts of the judiciary; however, in modern societies the need for protecting the defendant from the public and trial by media is becoming more and more necessary. The protection of the defendant%s right to privacy and his personality rights is of crucial importance, since disproportionate interference in these rights when reporting on criminal proceedings can undermine the fundamental guarantees of a fair criminal trial. The article analyses the constitutional and theoretical outlines for the protection of the defendant's personality rights with regard to media coverage of criminal matters. On this basis, the current regulation of media reporting on criminal proceedings in Slovenia is presented and some ideas for the change of the relevant legislation are introduced.
Keywords: človekove pravice; human rights; informiranje; kazenski postopek; kazniva dejanja; mass media; množični mediji; objektivnost; obveščanje; storilci